Pattern and risk factors of congenital anomalies among children attending Specialized Hospitals in Sohag Governorate - Ayman S. Abd El-Hady; Abdel-Nasser S. Mohammed; Mohammed A. Aladawy; Gamal E. Soliman (Al-Azhar Assiut Medical Journal)
Background Congenital anomalies (CAs) are a worldwide problem. They are important causes of childhood deaths, chronic illness, and disability. The WHO defined CAs as structural, functional, or metabolic anomalies that originate during intrauterine life and can interfere with the body’s functions. They result from defective embryogenesis or intrinsic abnormalities in the development process. Aim The present study aimed to Detect clinical patterns and risk factors CAs among children Attending Specialized Hospitals in Sohag Governorate. Patients and methods Matched case-control study was conducted was conducted during the period from March 2022 to September 2022 in the Pediatric clinic and Pediatric surgery clinics affiliated to Sohag University Hospital and Sohag Teaching Hospital (which provide tertiary health care). The sample size was 150 cases and 150 controls. The study targeted all the infants (less than 1 year) from birth to hospital discharge. The cases with CAs were identified through clinical, radiological, ultrasound, or echocardiography. Results The study revealed that Cardiac malformations came first by (26.6%) mostly as cardiac septal defects (15.3%), Chromosomal defects came second by (22%), Neural tube defects (12%) Oral cleft defects (10.6%), Genitourinary defects (8.6%) and Digestive system anomalies by (4.6%). Applying the binary logistic analysis, the risk factors for CAs were consanguineous parents, inadequate antenatal care, advanced maternal age, history of previous CA between relatives, Infants of diabetic mothers, rural residence, first birth order. Conclusion Cardiovascular, chromosomal CAs, Neural tube defects, oral clefts, Genitourinary system anomalies and digestive system anomalies were the most common CAs in this study. advanced maternal age, rural residence, positive consanguinity and inadequate antenatal care (poor attendance at antenatal clinics), First birth order, infants of diabetic mothers, family history of CA are at increased risk of having CAs.